A STUDY ON THE DIFFICULTIES IN GIVING ENGLISH ORAL PRESENTATIONS FACED BY SECOND-YEAR STUDENTS OF ENGLISH TEACHER EDUCATION MAJOR AT DANANG UNIVERSITY OF FOREIGN LANGUAGE STUDIES - Phạm Hoàng Minh Tâm (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
As doing presentations in English is one of the most important skills for an English teacher, this research was conducted on 42 second-year students of English Teacher Education major at Danang university of Foreign Language Studies to identify their difficulties in making English oral presentations and look for some common causes of the problems they were facing. The questionnaire was adapted from Nguyen Thi Van Ha’s research, the results were coded and analyzed using Excel 2016. Based on the results, the main difficulties faced by these pre-service teachers were grammatical usage, controlling their nerves and handling difficult questions from the audience. According to the students’ opinions, there were three causes which contributed to their difficulties: low level of English proficiency, lack of confidence and bad voice quality. Hopefully, the findings of this research will assist teachers as well as pre-service teachers in their career by enabling them to have better understanding of how to give a successful English oral presentation